Determination of foliar sampling conditions and standard leaf nutrient levels to assess mineral status of loquat tree - Quinones, Ana; Soler, Esteban; Legaz, Francisco (Taylor & Francis Group, 2020)
Loquat [Eriobotrya japonica (Thunb.) Lindl.] is a minor fruit-tree species which is grown commercially in the Mediterranean region. Given the current increase in loquat cultivation, there is a need to define basic crop-management procedures in order to obtain high yields and optimal fruit quality. The aim of this work was to develop a routine for loquat farmers to follow, in order to know the nutritional status of trees in order to establish a rational fertilization regime, and to correct nutrient deficiencies as soon as possible. This paper reports three experiments aimed at establishing: 1) leaf type, 2) time of leaf sampling and 3) the standard leaf nutrient levels as a function of maximum yield. Results indicate that the summer flush leaves could be the most representative of nutritional status. Thus, the most appropriate time to sample leaves for analysis is in summer (beginning of August to the end of September), taking mature 3–4 month old leaves.